Integrated Management of Sheath Blight Disease of Rice - Zacharia Geogy (Department of Plant Pathology, College of Agriculture, 1990)
The present investigation was undertaken to evolve an economically feasible management strategy integrating biological and chemical aspects of control measures of sheath blight disease of rice. An attempt has been made to identify a potential biocontrol agent to combat sheath blight disease causing considerable loss to rice cultivation. Another important aspect of the programme was to develop and easy and cheap method of assaying the population of R. solani in paddy soil. Among different techniques screened, floatation sieving using both Fenwick can and glass cylinder were effective in selective recovery and the latter was further modified using different concentrations of salt. Among selective media mineral antibiotic media amended with Fosetyl-al and in studies using different baits autoclaved straw bits were superior. Among the microorganisms isolated from rice soils of Thiruvananthapuram, Kerala, thirteen species of fungi were found to be antagonistic to R. solani. Among the antagonists, Trichoderma harzianum was found to be the best biocontrol agent against sheath blight disease. This was followed by T. koningii. A field study incorporating various soil amendments viz., neem cake and lime, Carbendazim and T. harzianum, a combination of amendments with Carbendzim and T. harzianum reduced disease severity and increased yield of grain and straw. These combinations also showed higher fungal and bacterial population and reduced R. solani population. Negative correlation between total fungi/bacteria and R. solani was observed suggesting inoculums reduction of the pathogen in critical growth stages of the crop. From the economic point of view, lime alone was found to have highest cost- benefit ratio compared to other treatments. The above result is possibly due to poor disease pressure observed during the investigation.